Realising universal maternity entitlements: lessons from Indira Gandhi Matritva Sahyog Yojana - Sinha, Dipa (2016)
n India, most of the work women do is invisible and unrecognised because it is done outside the boundaries of the formal economy. As a result, the laws pertaining to maternity entitlements reach a very limited number of women. The National Food Security Act, 2013 was the first national-level legislation to recognise the right of all women to maternity entitlements and wage compensation. Since the passage of the act, India has been using an existing conditional cash transfer scheme, the Indira Gandhi Matritva Sahyog Yojana, to implement this entitlement. An examination of the implementation of defined maternity entitlements under the act via a conditional cash transfer, highlights the failure of such a programme to uphold the spirit of the act. Amendments to the act are necessary to ensure that the most vulnerable women are able to realise their right to maternity entitlements, wage compensation, health and nutrition. - Reproduced.
Keywords: Maternity leave; Indira Gandhi Matritva Sahyog Yojana; Women